2016
DOI: 10.3748/wjg.v22.i33.7507
|View full text |Cite
|
Sign up to set email alerts
|

Hepatobiliary and pancreatic ascariasis

Abstract: Hepatobiliary and pancreatic ascariasis (HPA) was described as a clinical entity from Kashmir, India in 1985. HPA is caused by invasion and migration of nematode, Ascaris lumbricoides , in to the biliary tract and pancreatic duct. Patients present with biliary colic, cholangitis, cholecystitis, hepatic abscesses and acute pancreatitis. Ascarides traverse the ducts repeatedly, get trapped and die, leading to formation of hepatolithiasis. HPA is ubiquitous in endemic regions and in Kashmir, one such region, HPA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
160
1
12

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(174 citation statements)
references
References 46 publications
1
160
1
12
Order By: Relevance
“…the echogenic strips inside the ducts. Other signs include gallbladder and cystic duct distension, gallbladder wall edema, sludge inside the gallbladder, and multiple liver abscesses [32]. Retained worm fragments can serve as a nidus for biliary stones.…”
Section: Hepatobiliary-pancreatic Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…the echogenic strips inside the ducts. Other signs include gallbladder and cystic duct distension, gallbladder wall edema, sludge inside the gallbladder, and multiple liver abscesses [32]. Retained worm fragments can serve as a nidus for biliary stones.…”
Section: Hepatobiliary-pancreatic Systemmentioning
confidence: 99%
“…They may also present later as intrahepatic duct calculi due to recurrent biliary obstruction [46]. Ultrasound allows visualization of single worms, bundles of worms, or pseudotumor-like appearance [32,33,47]. The worms can be extracted endoscopically [48].…”
Section: Hepatobiliary-pancreatic Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that 25% of the global population is infected. 1 Ascaris eggs are usually transmitted to children while they are playing with soil. In adults, transmission may be through eating raw vegetables contaminated with sewage water.…”
Section: Introductionmentioning
confidence: 99%
“…It is acquired through the ingestion of matured ova in contaminated water, raw vegetables, and food [1][2][3].…”
mentioning
confidence: 99%